Fabrication of a Fabry-Pérot cavity in a microfluidic channel using thermocompressive gold bonding of glass substrates - Lear, Kevin L., author; Feld, Stewart A., author; Kumar, Dhiraj, author; Shao, Hua, author; IEEE, publisher (Colorado State University. Libraries, 2005)
This paper presents a simple, low-cost, and reliable process for the fabrication of a microfluidic Fabry-Pérot cavity in a Pyrex glass substrate. The microfluidic channels were etched in HF solution on a glass substrate using a Cr/Au/photoresist etching mask resulting in a channel bottom roughness of 1.309 nm. An effective thermocompressive gold-gold bonding technique was used to bond the photolithographically etched glass substrates inside a 350° C oven in a 10-3 torr vacuum. Pressure was applied to the glass pieces by using two aluminum blocks with intermediate copper sheets. This method takes advantage of using Cr/Au layers both as a wet etching mask and as intermediate bonding layers, requiring only one lithography step for the entire process. The fabrication method is also compatible with the incorporation of dielectric mirror coatings in the channels to form a high-finesse Fabry-Pérot cavity. A parallelism of 0.095 degrees was measured, and a finesse as high as 30 was obtained using an LED. The microfluidic cavity developed here can be used in electrophoresis and intracavity spectroscopy experiments.
Keywords: finesse; Fabry-Pérot cavity; gold thermocompressive bonding; microfluidics